2010
DOI: 10.1007/s10620-010-1483-z
|View full text |Cite
|
Sign up to set email alerts
|

Precut Fistulotomy for Difficult Biliary Cannulation: Is It a Risky Preference in Relation to the Experience of an Endoscopist?

Abstract: After therapeutic ERCP training involving at least 100 ERCPs, including at least half that were therapeutic cases and more than ten that were precut papillotomies, a precut fistulotomy can be performed safely and effectively in low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 33 publications
2
54
1
Order By: Relevance
“…A study of precuts in DBC reported that endoscopist experience with the precut procedure was important, particularly in experienced hands, no increasing the number of complications [6,7,16-18]. We used stricter DBC criteria to prevent frequent papillary contacts causing PEP (5-min cannulation time and 5 attempts at papillary contact) compared with a study which defined DBC as failure to achieve biliary access despite 10 min of attempted cannulation or more than 5 attempted unintentional pancreatic duct cannulations [6,19]. Of the DBC criteria, unintentional pancreatic duct cannulation more than 3 times indicated DGC, and subsequent PPS was attempted without delay when DGC failed, according to the algorithm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A study of precuts in DBC reported that endoscopist experience with the precut procedure was important, particularly in experienced hands, no increasing the number of complications [6,7,16-18]. We used stricter DBC criteria to prevent frequent papillary contacts causing PEP (5-min cannulation time and 5 attempts at papillary contact) compared with a study which defined DBC as failure to achieve biliary access despite 10 min of attempted cannulation or more than 5 attempted unintentional pancreatic duct cannulations [6,19]. Of the DBC criteria, unintentional pancreatic duct cannulation more than 3 times indicated DGC, and subsequent PPS was attempted without delay when DGC failed, according to the algorithm (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we applied the step-wise techniques early following the stricter DBC criteria, resulting in a higher technical success rate and reduced successful cannulation time compared with a previous our report (9.2 ± 7.3 minutes in our study vs . 16.9 ± 9.1 minutes, P  < 0.05) [6]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even so, the success rate of NKF is still low [8,9]. For another technique, NKPP, only pinkish or dark red bile duct has been mentioned in most literature without more details about the procedure [10].…”
Section: Discussionmentioning
confidence: 99%